ERROR ANALYSIS IN SOLVING APPLIED MATHEMATICS PROBLEMS BASED ON THE NEWMAN PROCEDURE - Nathasa Pramudita Irianti; Farah Dzil Barr; Lilis Nurasiah; Nur Aliyyah Irsal (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
The purpose of this study is to describe the various kinds of errors made by taruna when solving applied mathematics problems based on the Newman procedure. Newman divides errors into 5 types, namely reading error, comprehension error, transform error, process skill error, and encoding error. This research uses descriptive qualitative research methods. Data collection techniques were carried out using tests and interviews. Data reduction, data presentation, and verification or conclusion drawing are part of this research. Based on the results of research and data analysis, it can be seen that in solving mathematical problems in land mathematics courses there are 5% of subjects experience errors in reading errors, 16% of subjects experience errors in comprehension errors, 9% errors in transform errors, 26% of subjects experience process skill errors, and 9% errors in encoding errors. Most of the errors were errors in the selection of problem-solving strategies.